A novel nanoemulsion-based method to produce ultrasmall, water-dispersible nanoparticles from chitosan, surface modified with cell-penetrating peptide for oral delivery of proteins and peptides - Barbari GR (Dove Medical Press, 2017)
Ghullam Reza Barbari,1 Farid Abedin Dorkoosh,1 Mohsen Amini,2 Mohammad Sharifzadeh,3 Fateme Atyabi,1 Saeed Balalaie,4 Niyousha Rafiee Tehrani,5 Morteza Rafiee Tehrani1 1Department of Pharmaceutics, 2Department of Medicinal Chemistry, 3Department of Pharmacology, School of Pharmacy, Tehran University of Medical Sciences, 4Department of Chemistry, Khaje Nasiroddin University, 5Department of Biochemistry, School of Medicine, Tehran University of Medical Sciences, Tehran, Iran Abstract: A simple and reproducible water-in-oil (W/O) nanoemulsion technique for making ultrasmall (<15 nm), monodispersed and water-dispersible nanoparticles (NPs) from chitosan (CS) is reported. The nano-sized (50 nm) water pools of the W/O nanoemulsion serve as “nano-containers and nano-reactors”. The entrapped polymer chains of CS inside these “nano-reactors” are covalently cross-linked with the chains of polyethylene glycol (PEG), leading to rigidification and formation of NPs. These NPs possess excessive swelling properties in aqueous medium and preserve integrity in all pH ranges due to chemical cross-linking with PEG. A potent and newly developed cell-penetrating peptide (CPP) is further chemically conjugated to the surface of the NPs, leading to development of a novel peptide-conjugated derivative of CS with profound tight-junction opening properties. The CPP-conjugated NPs can easily be loaded with almost all kinds of proteins, peptides and nucleotides for oral delivery applications. Feasibility of this nanoparticulate system for oral delivery of a model peptide (insulin) is investigated in Caco-2 cell line. The cell culture results for translocation of insulin across the cell monolayer are very promising (15%–19% increase), and animal studies are actively under progress and will be published separately. Keywords: ultrasmall, cell-penetrating peptide, chitosan, oral insulin, nanoemulsion, Caco-2 cell